Süryani Ortodoks Kilisesi’ nde ibadet - Durak, Nihat (My University, 2000)
Tezin Giriş Bölümü'nde, konunun önemi, bu araştırmayla hedeflenen husus, araştırmanın metodolojisi ve araştırmaya esas teşkil edenler temel kaynaklar üzerinde duruldu. Süryâni Ortodoks Kilisesi ismini taşıyan birinci bölümde, bu kilisenin, Adı, Menşei, Tarihî Gelişimi, Günümüzdeki Durumu ve Temel Özellikleri anlatıldı. Süryâni Ortodoks Kilisesi'nde İbadetin Temel Unsurları adlı ikinci bölümde, bu kilisedeki, İbadet, Dua, Mabet, İbadet Dili, İbadet-Musiki İlişkisi, İbadette Yön, İbadette Kitab-ı Mukaddes'in Yeri kavramları üzerinde duruldu. Ayrıca, İbadette Kullanılan Eşya ve Malzemeler ile Kilise'nin İç Yapısı ve İbadette Kullanılan Bölümleri anlatıldı. Üçüncü Bölüm'de, Süryâni Ortodoks Kilisesi'nde Namaz, Oruç, Kutsal Ziyaret, Ondalık, Sadaka ile Dinî Gün ve Bayramlar üzerinde duruldu. Sakramentler adını taşıyan dördüncü bölümde, Genel olarak Sakrament kavramı işlendikten sonra, ayrıntılı bir biçimde, Süryâni Ortodoks Kilisesi'nde, Vaftiz, Komfirmasyon, Tevbe, Evharistiya, Ruhban Takdisi, Nikâh (Evlilik) ve Hasta Yağı Sakramentleri ve Bu Sakramentlerin Uygulanış Usûlleri anlatıldı. Tezin genel bir değerlendirilmesinin yapıldığı sonuç bölümüyle, bu çalışma bitirildi. Ekler bölümünde ise, ibadette kullanılan eşya ve malzemelerle, kilisenin ibadette kullanılan bölümlerinin resimleri yer almaktadır.

The main subject matter of the introductory chapter of this thesis is on importance of subject, the methodology of this, the thing aimed by this study and fundamental sources that are based for this investigation. The name of this church, its origin, its historical development, its present situation, and its fundamental properties were told in the first chapter named as Syrian Orthodox Church. In the second chapter named as Fundamental Properties of Worshipping in the Syrian Orthodox Church , the subject were on the concepts of the worshipping, praying, temple, language used in worship, worship - music relation, direction (Kıblah) in the worship, the place of the Old and New Testament. Besides these, the materials and wares used in worshipping and the internal structure of the church and sections in worship are introduced to the reader. In the third chapter, the praying (Slutho), fasting, diet, holy visit, a tenth tax to church, alms, religious days and holydays were mentioned. The sacraments in the Syrian Orthodox Church are the subject of the fourth chapter. Under this title, after the concept of the sacraments were explained in general, the scarements related to the babtism, confirmation, reconciliation and confession, communion (eucharist), order, wedding (marriage) and unction were explained in detail according to its theory and ways of practice. The work ends by a conclusion chapter in which a general final evaluation of the thesis is given. In the annexes section, the pictures and photos of monasteries and churches, the pictures related to the inside and outside of churches, like the bell tower, and the photos of wares and materials used in the worship which has a special importance in Syrian Orthodox Church prays are given.
Keywords: Cemaat yönetimi; Din; Hristiyanlık; İbadet; KİLİSELER_TÜRKİYE; Ortodoks kilisesi; Süryaniler_Türkiye